Upaya Penambahan Thoracic Mobilization pada Mckenzie Exercise Lebih Baik dalam Menurunkan Disabilitas dan Meningkatan Mobilitas Fleksi Pinggang pada Nyeri Pinggang Diskogenik - Ginting, Isaharpika Br; Purba, Yeni Trisna; Saragih, Febrina Sani (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2024)
This study aims to prove the addition of thoracic mobilization to McKenzie exercise interventions is better than McKenzie exercise against disability and waist mobility in dichogenic low back pain. This study was conducted on patients diagnosed with lumbar disogenic low back pain at the Cengkareng Regional General Hospital. Method: This study is quasi-experimental and uses purposive sampling techniques. It consists of 16 samples divided into two groups. The treatment group was given the addition of thoracic mobilization to the McKenzie exercise and the control group was given the addition of thoracic mobilization to the McKenzie exercise and the control group was given the McKenzie exercise only. Results: Shapiro Wilk-test normality test with p-value>α (0.05), Levene's homogeneity test with p-value> α (0.05). Independent t-test results showed significant differences in effects in both groups, namely a p=0.005 value for the disability scale and a p=0.019 value for the mobility scale (p<α(0.05)). Conclusion: The combination of thoracic mobilization and McKenzie exercise can lower disability and improve waist flexion mobility. McKenzie exercise can lower disability and improve waist flexion mobility. The addition of thoracic mobilization to McKenzie exercise is better at reducing disability and improving waist mobility than McKenzie exercise alone.